Inter-se Distribution Criteria and the Union Finance Commissions: A View from Kerala - Shaheena.P (KILA Journal of Local Governance, 2014)
The Union Finance Commission (UFC) and State Finance Commissions (SFCs) are the constitutional authorities entitled to transfer resources to the third tier. Despite the progress, not only that the share of the state remained low in the UFC dispensations but the share of the state even declined from 4.54 percent of Twelfth UFC (UFC- XII) to 3.11 percent in the awards of Thirteenth UFC (UFC- XIII). Kerala suffered heavily on the inter- se distribution criteria. The paper examines the inter se distribution criteria of the UFCs of India towards LGs, to delineate the criteria that worked against the interests of Kerala.